From 9/11 to 10/7: Netanyahu’s Metaphor Transforming Terror into a Moral Narrative - Fizzah Khan; Awais Bin Wasi; Sohail Ahmed (ASIAN Journal of International Peace & Security (AJIPS), 2025)
The paper presents a case study on metaphorical expressions of Netanyahu, examining how war crimes, violence, and morality are embedded within a metaphorical framework. The paper aims to contribute towards a better post-9/11 metaphorical analysis of "Israel-Palestine conflict" through a close examination of the video recording of Netanyahu’s address, focusing specifically on strategies of positive selfpresentation, "Us-Them," strategies, to make violence appear legitimate. The research paper further uses a Political Discourse Analysis tool conceptualized by Teun A. Van Dijk, to identify how this metaphorical appropriation can help identify Netanyahu’s cover mechanism, where terrorists past historical strategies are likened to cement a political ideology. Within this broader metaphorical construct, this paper interprets a qualitative research design where textual analysis of the metaphorical representation is presented. The result of this paper explains how metaphorical conceptualization can help create a division to position people both as victims and terrorists, besides metaphorical usage to frame terrorism as a threat to humanity. The paper further contributes towards enhancing our knowledge of metaphorical usage within a post9/11 construct, and helps to identify how metaphoric conceptualization can create opportunities for politicians to frame terrorism within a threat construct.